Prevalência de dermatite atópica e fatores associados em uma coorte prospectiva aos dois anos de vida - Guimarães, Tassia Cecília Pereira (2024)
Background Atopic Dermatitis, a chronic inflammatory skin disease, is influenced by genetic and environmental factors, triggering dysregulated immune responses, with its main manifestation being eczema. The global incidence varies from 10 to 20%, and risk factors include dysfunction of the skin barrier, genetic predisposition, early exposure to allergens, and air pollution, among others. Objective To establish the prevalence of atopic dermatitis in the second year of life in children born in the city of Uberlândia/MG. Methods This is a prospective study that assessed the prevalence of Atopic Dermatitis at 2 years of age in children born in Uberlânida/MG. Between 2019 and 2022, it was carried out through the follow-up of newborns from two public maternity hospitals in the city of Uberlândia, in the central region of Brazil, including the following steps: (1) birth interview, (2) follow-up telephone interview after 12 months, (2) follow-up telephone interview after 24 months. Results The initial sample included 3373 newborns, of which 2099 were followed up after 12 months and 960 after 24 months. Of these, 145 were classified with Atopic Dermatitis, resulting in a prevalence of 15.1%, aligned with European and Latin American studies. The study did not identify a significant association between evaluated genetic and environmental risk factors, which may be justified by Atopic Dermatitis being assessed at a very early stage and differently from other studies. Symptoms impacted sleep quality in 37,24% of children, highlighting the clinical importance of this symptom on the patient's quality of life. Conclusion This study contributes to reinforcing the importance of appropriate and early diagnosis, as the symptoms and its consequences, such as itching and impact on sleep quality, are present in almost half of the patients. These discomforts for the patient and their families could be minimized by early diagnosis and proper management of Atopic Dermatitis.